2009
DOI: 10.1073/pnas.0903103106
|View full text |Cite
|
Sign up to set email alerts
|

Potential etiologic and functional implications of genome-wide association loci for human diseases and traits

Abstract: catalog ͉ evolution ͉ GWAS ͉ polymorphism ͉ disorders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
3,502
7
25

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,748 publications
(3,580 citation statements)
references
References 19 publications
46
3,502
7
25
Order By: Relevance
“…Advances in genotyping technologies have facilitated genome-wide association studies and have contributed to the identification of thousands of SNPs associated with disease 1 . However, most of the associated SNPs explain a modest proportion of heritability for most common diseases, 2 and they do not provide variants directly applicable for diagnosis, prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in genotyping technologies have facilitated genome-wide association studies and have contributed to the identification of thousands of SNPs associated with disease 1 . However, most of the associated SNPs explain a modest proportion of heritability for most common diseases, 2 and they do not provide variants directly applicable for diagnosis, prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…All the published GWAS have been cataloged in the National Human Genome Research Institute 'A Catalog of Published Genome-Wide Association Studies' (http://www.genome.gov/gwa studies/) and this resource includes only those studies that attempted to genotype at least 100 000 SNPs in the initial stage. 3 As a result, the AMD study by Klein et al 1 was recorded as the first entry in the catalog and was generally being recognized as the first GWAS.…”
Section: Gwas Before Hapmapmentioning
confidence: 99%
“…Instead, most of the disease-associated risk alleles conferred small effect sizes (OR o1.5). 2,3 The finding of not many large effect size variants is expected, as the purifying selection pressure will remove them from the populations or keep their population frequencies low. However, GWAS is not a powerful approach for studying rare or uncommon SNPs (regardless of their effect sizes), because they are poorly represented in the commercial whole genome genotyping arrays.…”
Section: Introductionmentioning
confidence: 99%
“…11 GWAS and meta-analysis of GWAS have also identified metabolic syndrome trait-associated genetic variations, including obesity, type 2 diabetes, dyslipidemia and hypertension. 12 We have previously reported that among the single-nucleotide polymorphisms (SNPs) susceptible to obesity, [13][14][15] rs7498665 in the SH2B adaptor protein 1 (SH2B1) gene was associated with VFA, 16 and that among hypertension-susceptible SNPs, 17,18 rs1004467 in the cytochrome P450, family 17, subfamily A, polypeptide 1 (CYP17A1) gene and rs11191548 in the 5¢-nucleotidase, cytosolic II (NT5C2) gene were significantly associated with both reduced VFA and SFA in women, indicating a genetic background to central obesity. 19 Visceral fat obesity is also a risk factor for the development of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%